MANAJEMEN KESISWAAN DALAM MENGEMBANGKAN BUDAYA LITERASI DIGITAL SISWA - Wahyuni, Heru; Burhan Eko Purwanto; Sutji Muljani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Digital literacy development is the idea of the development of technology and information. The development of digital literacy programs in schools needs to be done appropriately through good student management. Where in the preparation of a program carried out by student management needs to go through several stages, namely planning, organizing, directing, and supervising. The research was conducted by conducting a literature study, namely by analyzing several journals and articles from previous research. Based on previous research, it shows that the implementation of the digital literacy program has not been fully implemented optimally. This can be caused by several determining factors other than the research variables that have been determined, so researchers cannot specifically indicate the determining factors for the lack of maximization of the program.